Design of hollow tapered PMMA polymeric microneedles for enhanced structural stability and drug delivery efficiency - Aswani Kumar Gera; Rajesh Kumar Burra (AIP Advances)
Microneedles have emerged as a promising alternative to conventional, or so-called hypodermic, needles for transdermal drug delivery. A meticulous design of microneedle geometry is crucial for balancing mechanical stability and fluid flow of drugs through these microneedles. This research paper analyzes the mechanical performance and fluid flow behavior of hollow cylindrical tapered shaped microneedles with polymethyl methacrylate, a biocompatible polymer, as material, considering its mechanical properties and also the material being widely used in biomedical applications. The finite element analysis tool is used to enhance the microneedle design by varying the outer base radius and tip radii to mitigate the von Mises stress that is exhibited during axial load and bending load conditions. In addition, microfluidic analysis is to assess the fluid flow behavior through the hollow microneedles, measuring the flow rates of fluids (water, glucose, and insulin).Simulated results reveal that an axial stress of 3.26 × 106 N/m2 and bending stress of 2.31 × 107 N/m2 were reported, which are below the yield strength of the material and satisfy the criteria for successful microneedle penetration. Flow rate analysis of water reports that 834.42 μl/min and 5396.94 μl/min and for glucose as 412 μl/min and 3648 μl/min, and that of insulin as 834 μl/min and 5244 μl/min for applied inlet pressure of 10 and 100 kPa, respectively. The flow rates reveal that water and insulin exhibit nearly identical flow rates, indicating that the proposed microneedles are capable of efficiently delivering viscous fluids.